2018
DOI: 10.3329/bjar.v42i4.35790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermented tea extract in controlling brown spot and narrow brown spot of rice

Abstract: Compost tea, Tilt 250 EC and Bavistin 50 WP were evaluated for controlling brown spot and narrow brown spot diseases of rice in the field laboratory of the Department of Plant Pathology, Bangladesh Agricultural University, Mymensingh during the period from July to December, 2011. Significant effect of different treatments was observed on the severity of brown spot and narrow brown spot of rice as compared to control. The results evidently showed the lowest brown spot severity in T4 (Tilt 250 EC applied as foli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In case of severe infection of NBLS disease, spraying of Tilt (Propiconazole) was helpful to avoid great loss of yield when applied in the booting phases (Zhou and Jo, 2014) which are proved by the results of current studies that sprays at early and late booting growth phases are more effective than spray at soft dough or heading phase. In a comparative study, Propiconazole was found quite effective as spray and soil drenching in the booting phase (Sultana et al, 2017). The fungicide Proud (Propiconazole) 25 EC 0.1% exhibited minimal disease severity in dough and maturity stages, respectively (Tuli et al, 2017) which are also proved in the present studies that spray at soft dough phase was proved less effective against the severity of NBLS disease.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In case of severe infection of NBLS disease, spraying of Tilt (Propiconazole) was helpful to avoid great loss of yield when applied in the booting phases (Zhou and Jo, 2014) which are proved by the results of current studies that sprays at early and late booting growth phases are more effective than spray at soft dough or heading phase. In a comparative study, Propiconazole was found quite effective as spray and soil drenching in the booting phase (Sultana et al, 2017). The fungicide Proud (Propiconazole) 25 EC 0.1% exhibited minimal disease severity in dough and maturity stages, respectively (Tuli et al, 2017) which are also proved in the present studies that spray at soft dough phase was proved less effective against the severity of NBLS disease.…”
Section: Discussionsupporting
confidence: 71%
“…The sprays during booting stages proved more effective in a multi-year studies . In a comparative study, Propiconazole was found quite effective as spray and soil drenching in the booting phase compared to Baviston and compost tea (Sultana et al, 2017). Propiconazole significantly reduces fungal infections on rice crop (Gupta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%